Application of the Pitzer theory to the evaluation of pH of the phthalate standard solution - Mendonça, António (2022)
The pH value of the potassium hydrogen phthalate 0.05 mol.kg-1 has been detemined, using the Bates-Guggenheim convention and lhe Pitzer model for the calculation of the chloride íon activity coefficient. A comparison has been made between lhe two approaches.